Piping engineering : preventing fugitive emission in the oil and gas industry - Sotoodeh, Karan (John Wiley & Sons, Inc., 2023)
Piping Engineering: Preventing Fugitive Emission in the Oil and Gas Industry is a practical and comprehensive examination of strategies for the reduction or avoidance of fugitive emissions in the oil and gas industry. The book covers key considerations and calculations for piping and fitting design and selection, maintenance, and troubleshooting to eliminate or reduce emissions, as well as the various components that can allow for or cause them, including piping flange joints. The author explores leak detection and repair (LDAR), a key technique for managing fugitive emissions. He also discusses piping stresses, like principal, displacement, sustained, occasional, and reaction loads, and how to calculate these loads and acceptable limits. Various devices to tighten the bolts for flanges are described, as are essential flange fabrications and installation tolerances. The book also includes: Various methods and calculations for corrosion rate calculation, flange leakage analysis, and different piping load measurements; Industry case studies that include calculations, codes, and references; Focuses on critical areas related to piping engineering to prevent emission, including material and corrosion, stress analysis, flange joints, and weld joints; Coverage of piping material selection for offshore oil and gas and onshore refineries and petrochemical plants.